The effect of TikTok Shop algorithm and Payday Sale period on conversion rate among Generation Z in Bali - Ni Putu Cahya Wati; Nyoman Sri Subawa (Priviet Social Sciences Journal, 2026)
Advances in digital technology have transformed social media into an essential marketing and transactional ecosystem that increasingly influences consumer behavior, particularly among Generation Z in Indonesia where TikTok Shop has become a dominant social commerce platform driven by algorithmic personalization and creative content strategies. This study aims to analyze the effect of TikTok algorithm personalization and creative content on conversion rates, as well as to examine the moderating role of the Payday Sale period among Generation Z consumers in Bali. This research employs a quantitative explanatory design using primary data collected through an online questionnaire distributed to 250 Generation Z respondents in Bali who actively use TikTok and have experienced the Payday Sale promotion. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.0, including outer model and inner model evaluation and bootstrapping for hypothesis testing. The results show that TikTok algorithm personalization has a positive and significant effect on conversion rate, indicating that more accurate content recommendations increase purchase likelihood. Similarly, creative content significantly enhances conversion rate by improving user engagement and purchase intention. Furthermore, the Payday Sale period significantly strengthens the relationship between algorithm personalization and creative content toward conversion rate, indicating that promotional momentum amplifies the effectiveness of digital marketing stimuli. In conclusion, TikTok algorithm personalization and creative content are key determinants of conversion rate among Generation Z consumers in Bali, while the Payday Sale period acts as a reinforcing factor that enhances both variables in driving purchase conversion behavior on TikTok Shop.